How to write better essays - Greetham, Bryan (London : Red Globe Press, 2018)
This guide takes students through each step of the essay writing process, enabling them to tackle written assignments with confidence. Students will develop their ability to analyse complex concepts, evaluate and critically engage with arguments, communicate their ideas clearly and concisely and generate more ideas of their own. Chapters are short and succinct and cover topics such as reading purposefully, note-taking, essay writing in exams and avoiding plagiarism.
Includes bibliographical and index.
Keywords: English language -- Rhetoric; Exposition (Rhetoric).; Essay -- Technique